Overweight in youth and sleep quality: is there a link? - Pacheco SR1, SR (2018)
OBJECTIVE: Overweight seems to be related to a higher prevalence of sleep disturbances. Decreased sleep duration and altered sleep quality are risk factors for obesity. Our aim was to compare the sleep pattern of overweight children with that of a matched control group and assess the relationship between sleep quality and obesity. MATERIALS AND METHODS: Retrospective cohort study comparing 41 overweight children with a normal-weight control group, both submitted to polysomnography. The samples were matched for age, sex, and apnea-hypopnea index. Body mass index (BMI) z-scores were calculated using World Health Organization (WHO) growth charts. Insulin resistance in the study group was determined using the homeostatic model assessment for insulin resistance (HOMA-IR). Sleep patterns were compared. The statistical analysis was performed using SPSS® version 21. RESULTS: The mean age (± standard deviation) of the population was 10 ± 3.4 years (min. 5 years; max. 17 years). Fifty-six percent of the participants in both groups were girls. N3% was lower in the study group (18.95 ± 6.18%) compared with the control group (21.61 ± 7.39%; t (40) = 2.156, p = 0.037). We found a correlation in the study group between HOMA-IR and N3% (Rs = -0.434, p = 0.008). CONCLUSION: The present study suggests a link between overweight/obesity and altered sleep quality due to compromised non-rapid eye movement sleep, an indirect marker of sleep quality. There was also a link between slow-wave sleep duration and insulin resistance. We must find a strategy to provide adequate slow-wave sleep duration to reduce the obesity epidemic at young ages. Further research is needed.